Observations of three-dimensional ionospheric plasma properties in a space hurricane - Lu, Sheng; Xing, Zan-Yang; Zhang, Qing-He; Zhang, Yongliang; Oksavik, Kjellmar; Lyons, L. R.; Lockwood, Michael; Ma, Yu-Zhang; Wang, Xiang-Yu; Balan, N.; Yang, Hui-Gen; Wang, Yong; et al. (Frontiers in Astronomy and Space Sciences, 2024)
The space hurricane is a newly discovered large-scale three-dimensional magnetic vortex structure that spans the polar ionosphere and magnetosphere. It has been suggested to open a fast energy transport channel for the solar wind to invade Earth’s magnetosphere under northward interplanetary magnetic field (IMF) conditions. It is, therefore, an important phenomenon to understand the solar wind–magnetosphere–ionosphere coupling process under northward IMF conditions. In this study, we report the three-dimensional ionospheric plasma properties of a space hurricane event in the Northern Hemisphere observed by multiple instruments. Based on the convection velocity observations from ground-based radars and polar satellites, we confirm that the major modulation to the polar cap convection called a space hurricane rotates clockwise at the altitude of the ionosphere. Ground-based incoherent scatter radar and polar satellite observations reveal four features associated with the space hurricane: 1) strong plasma flow shears and being embedded in a clockwise lobe convection cell; 2) a major addition to the total energy deposition in the ionosphere–thermosphere system by Joule heating; 3) downward ionospheric electron transport; and 4) multiple ion-temperature enhancements in the sunward velocity region, likely from the spiral arms of the space hurricane. These results present, first, the impact of space hurricane on the low-altitude ionosphere and provide additional insights on the magnetospheric impact on structuring in the polar ionosphere.